Educational Supervision as Improving the Quality of Learning in Schools: Systematic Literature Review - Mutiara, Gita (PPSDP International Journal of Education, 2025)
Educational supervision is a crucial effort in improving the quality of learning in schools. Through the supervision process, school principals, education supervisors, and other educators can provide guidance, evaluation, and constructive direction to enhance the effectiveness of the learning process. This study aims to examine the role of educational supervision in improving the quality of learning in schools, focusing on the implementation of effective supervision strategies and techniques. The results of the study indicate that educational supervision, when conducted in a structured and continuous manner, can enhance teachers’ teaching skills, improve the interaction between students and teachers, and create a more conducive learning environment. Therefore, educational supervision plays a vital role in improving and developing the quality of learning in schools, which ultimately has a positive impact on students’ academic achievements. This study is expected to serve as a reference for educators and education managers in designing more effective supervision policies and programs in schools.